2020
DOI: 10.1038/s41467-020-16280-y
|View full text |Cite
|
Sign up to set email alerts
|

Conserved protein Pir2ARS2 mediates gene repression through cryptic introns in lncRNAs

Abstract: Long non-coding RNAs (lncRNAs) are components of epigenetic control mechanisms that ensure appropriate and timely gene expression. The functions of lncRNAs are often mediated through associated gene regulatory activities, but how lncRNAs are distinguished from other RNAs and recruit effector complexes is unclear. Here, we utilize the fission yeast Schizosaccharomyces pombe to investigate how lncRNAs engage silencing activities to regulate gene expression in cis. We find that invasion of lncRNA transcription in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Nevertheless, polyadenylation isolation protocols consistently detect centromeric transcripts across kingdoms ( Table 1 ), providing evidence that cenRNAs can be processed like lncRNAs and mRNAs. These two latter groups of transcripts also tend to undergo splicing events to produce mature transcripts [ 91 , 92 ]. Indeed, centromeric RNAs are associated with splicing factors ( Table 1 ).…”
Section: Centromeric Transcriptionmentioning
confidence: 99%
“…Nevertheless, polyadenylation isolation protocols consistently detect centromeric transcripts across kingdoms ( Table 1 ), providing evidence that cenRNAs can be processed like lncRNAs and mRNAs. These two latter groups of transcripts also tend to undergo splicing events to produce mature transcripts [ 91 , 92 ]. Indeed, centromeric RNAs are associated with splicing factors ( Table 1 ).…”
Section: Centromeric Transcriptionmentioning
confidence: 99%
“…machinery and chromatin-modifying enzymes (Figure 3b) [78]. As such, mutations in cisacting cryptic introns or of the above-mentioned trans-acting factors result in a substantial increase in the expression of downstream genes (e.g., byr2+).…”
Section: Transcription Termination Of the Lncrna Nam1 Protects Expression Of The Downstream Gametogenic Byr2+ Genementioning
confidence: 99%
“…As such, mutations in cisacting cryptic introns or of the above-mentioned trans-acting factors result in a substantial increase in the expression of downstream genes (e.g., byr2+). Importantly, sporulation defects due to byr2+ repression by increased nam1 levels in cells lacking the exosome component Rrp6 [34] are rescued upon the mutation of Pir2 or splicing factors [78]. Thus, the regulation of nam1 termination provides a highly flexible, lncRNA-dependent system for cells to control commitment to meiosis.…”
Section: Transcription Termination Of the Lncrna Nam1 Protects Expression Of The Downstream Gametogenic Byr2+ Genementioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that CBC complex component NCBP1 promotes NMD in the cytoplasm 9,18 . Additional studies have reported the interaction between ARS2 and several components of the NMD pathway 5,19,20 . However, the question of whether ARS2 participates in NMD has not been addressed.…”
Section: Introductionmentioning
confidence: 99%